Neighborhood Context and Binge Drinking by Race and Ethnicity in New York City. (10th March 2016) - Chauhan, Preeti; Ahern, Jennifer; Galea, Sandro; Keyes, Katherine M.
Abstract : Background: Neighborhood context is associated with binge drinking and has significant health, societal, and economic costs. Both binge drinking and neighborhood context vary by race and ethnicity. We examined the relations between neighborhood characteristics—neighborhood norms that are accepting of drunkenness, collective efficacy, and physical disorder—and binge drinking, with a focus on examining race and ethnic‐specific relationships. Methods: Respondent data were collected through 2005 random digit‐dial‐telephone survey for a representative sample of New York City residents; neighborhood data were based on the 2005 New York City Housing and Vacancy Survey. Participants were 1, 415 past‐year drinkers; Whites ( n  =   877), Blacks ( n  =   292), and Hispanics ( n  =   246). Generalized estimating equations were used to estimate population average models. Results: For the overall sample, neighborhood norms that were more accepting of drunkenness were associated with greater binge drinking (odds ratio [OR]   =   1.22; 95% confidence interval [CI]   =   1.09, 1.37); collective efficacy and physical disorder were not significant. However, when examining this by race/ethnicity, greater collective efficacy (OR   =   0.75; 95% CI   =   0.62, 0.91) and greater physical disorder (OR   =   0.76; 95% CI   =   0.62, 0.93) were associated with less binge drinking for Whites only. Neighborhood norms that were more accepting of drunkenness were associated with binge drinking among Whites (OR   =   1.20; 95% CI   =   1.05, 1.38) and, while not significant (perhaps due to power), the associations were similar for Hispanics (OR   =   1.18; 95% CI   =   0.83, 1.68) and slightly lower for Blacks (OR   =   1.11; 95% CI   =   0.67, 1.84). Conclusions: Overall, results suggest that neighborhood characteristics and binge drinking are shaped, in part, by factors that vary across race/ethnicity. Thus, disaggregating data by race/ethnicity is important in understanding binge drinking behaviors. Abstract : We examined the relations between neighborhood norms that are accepting of getting drunk, collective efficacy, and physical disorder and binge drinking, with a focus on race and ethnicity. Greater collective efficacy and greater physical disorder were associated with less binge drinking for Whites only. Neighborhood norms that are more accepting of getting drunk were associated with binge drinking among Whites and, while not significant (perhaps due to power), the associations were similar for Hispanics and slightly lower for Blacks.